Faktor-Faktor yang Mempengaruhi Kinerja Pemasaran pada Usaha Mikro, Kecil dan Menengah (UMKM) Batik di Kampung Batik Laweyan dan Kampung Batik Kauman Surakarta - Dinna Riana (Common Publisher, 2019)
Batik industry players are developing and competing very tightly in marketing their products. Maintaining cultural heritage as a center for batik making is very hard, while government policies support the exploitation of national local wisdom, allowing batik to be produced in every region. This study is to determine Market Orientation, Product Innovation, and Entrepreneurship Orientation to Marketing Performance in Micro, Small, and Medium Enterprises (MSMEs) Batik in Kampung Batik Laweyan and Kampung Batik Kauman Surakarta. This type of research is quantitative. Primary data collection method. Sampling using purposive accident random sampling technique, the number of samples is 100 respondents. The results of the validity and reliability test show that all the questions posed are valid and reliable. The results of the multiple linear regression equation with the independent variable have a positive effect. The t-test results show that the variable Product Innovation and Entrepreneurship Orientation have a significant effect, while Market Orientation has no significant effect on Marketing Performance. The results of the F test show that all independent variables simultaneously affect Marketing Performance. The test results of the coefficient of determination (R2) show that the adjusted R square value is 0.626. It can be concluded that the independent variables (Market Orientation, Product Innovation, and Entrepreneurship Orientation) can explain the dependent variable, namely Marketing Performance of 62.6%. While the remaining 37.4% explained other factors that were not examined in this study.